Emotion-Focused Teaching Differs Across Preschool Activity Settings - Timothy W. Curby; Katherine M. Zinsser; Rachel A. Gordon; Emma G. Casey (SAGE Publishing, 2024)
This study explores how observed emotion-focused teaching in preschool classrooms differs across classroom activity settings. Forty-three teachers were observed across several mornings. A total of 1,604 video cycles were coded for levels of emotion-focused teaching (e.g., total, modeling, responding, and instructing) and their activity settings (e.g., mealtimes and transition). Activity settings seemed to afford-to varying degrees for different teachers-the opportunity to interact with children around their emotional learning. Small-group activity settings had the highest levels of emotion-focused teaching, and mealtimes had the lowest. Emotion instructing occurred most often during whole-group interactions, and emotion modeling occurred most often during children's independent work. Findings can inform the creation and implementation of professional development to promote these emotion-focused teaching practices. While research is increasingly demonstrating the value of emotion-focused teaching, understanding the variability of such practice over the various activity settings may identify opportunities to enhance the intentional support of children's emotional learning.